A study on non-compliance to treatment in a Chennai based diabetic population - Prithika, U. Yashila; P. Paul, Christina Mary; Nethaji, Vishwanath Simha; Vishnu, S.; Rumaiza, Wajeeha; Manoharan, Sangeetha; Meghna, M.; Vivek, K. (International Journal Of Community Medicine And Public Health, 2018)
Background: India is world’s diabetic capital. Treatment compliance is most important to manage the disease effectively. This study was done to estimate the prevalence of treatment non–compliance among the adult diabetic population and to identify certain risk factors that may be associated with it. Methods: The study was done on 300 diabetics who were chosen through stratified random sampling from urban and rural areas. Information was collected through a questionnaire that had questions on background information of the subject and then on diabetes and treatment compliance. The data entry and analysis were done using statistical package for social sciences (SPSS) version 22. The final data was summarized into percentages and 95% C.I was calculated for the prevalence rates. Cross tabulations were done for various variables. Chi-square values were calculated wherever appropriate and p values were based on the 2 –tailed values. Associations were assessed and 95% confidence interval of odds ratios were found using Epi Info version 7.1.2. Results: The overall prevalence of non-compliance to treatment in diabetics was found to be 29.7% with a 95% CI of 24.5-34.8%. Treatment non–compliance among diabetics was significantly higher among male subjects, subjects from joint families, subjects with family history of diabetes and also subjects with BMI in the normal range. Conclusions: This study shows the high prevalence rates of treatment non–compliance among the diabetic population emphasizes on the need for effective public–private partnerships to effectively reduce the disease burden of diabetes.